Characterization of PHBV films loaded with FO1 bacteriophage using polyvinyl alcohol-based nanofibers and coatings: a comparative study - Costa, Maria J. (2021)
There is a current demand for novel active food packaging solutions using biodegradable materials and no chemical antimicrobial compounds, to ensure food quality and safety. This work involved the incorporation of Salmonella Enteritidis bacteriophage Felix O1, for potential use as an anti-Salmonella agent, into polyvinyl alcohol (PVOH) coatings and fibers deposited by casting and electrospinning on polyhydroxybutyrate/polyhydroxyvalerate (PHBV) films. PHBV films (pristine, with coating, and with nanofibers) were characterized in terms of water sensitivity, mechanical performance, morphology, and thermal properties. Additionally, X-ray diffraction and Fourier Transform Infrared Spectroscopy were performed to assess possible chemical modifications on PHBV films after PVOH deposition and the presence of bacteriophage. PVOH increased the moisture content from 5.98% (PHBV) to 8.94% and 8.28% for PHBV/coating films and PHBV/nanofiber films respectively, increased the solubility from 0% (PHBV) to 30.32% (PHBV/coating films) and to 32.42% (PHBV/nanofiber films), and increased the hydrophilicity of the films (contact angle of 76.31° for PHBV, 64.01° for PHBV/coating films and 30.90° for PHBV/nanofiber films), leading to an increased water affinity of their surface. Felix O1 was successfully added and maintained antimicrobial activity (106 titer) after the formation of the coating and nanofibers, demonstrating that these solutions can potentially be used in future packaging materials to avoid Salmonella contamination.